2004
DOI: 10.1001/archneur.61.7.1114
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Stroke During Sexual Intercourse

Abstract: Background:The association between patent foramen ovale (PFO) and stroke risk in young adults is controversial and poorly understood. Paradoxical embolization through a PFO represents a possible mechanism by which PFO might predispose to stroke.Objective: To describe 4 patients with PFO who experienced the onset of ischemic stroke during sexual intercourse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…There are a few reports of ischemic strokes occurring during situations that produced an increase in ITP in patients with PFO, as in our cases 2 and 3 (i.e., while playing a wind instrument or during sexual intercourse) 3,4. These reports suggest that the increase in ITP was the probable pathophysiological step that ultimately led to paradoxical embolism.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…There are a few reports of ischemic strokes occurring during situations that produced an increase in ITP in patients with PFO, as in our cases 2 and 3 (i.e., while playing a wind instrument or during sexual intercourse) 3,4. These reports suggest that the increase in ITP was the probable pathophysiological step that ultimately led to paradoxical embolism.…”
Section: Discussionsupporting
confidence: 55%
“…Its hemodynamic effects have been studied extensively during the Valsalva maneuver 1. Recent studies have suggested that paradoxical embolization through a patent foramen ovale (PFO), caused by elevated ITP, could lead to stroke 2-4. However, very little is known about the effects of raised ITP on the incidence of stroke.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in intrathoracic, central venous, and right atrial pressures that occurs during Valsalva, and likely intercourse, potentiates right-to-left shunting through a PFO during those instances when the pressure in the right atrium exceeds that of the left atrium. However, the augmentation of right-to-left shunting that occurs with the Valsalva maneuver may be less important than shunting at rest as was present in our patient and the series by Becker et al 5 Furthermore, our patient had an associated septal aneurysm that demonstrated dramatic mobility with respiration. The size of the PFO, mobility of the septal aneurysm, and a resting right-to-left shunt may be the important factors that facilitated cerebral embolization during sexual intercourse in our patient.…”
Section: Discussionmentioning
confidence: 41%
“…Additionally, elevation of chest pressure during sexual intercourse may result in thrombus entering into left heart from right atrium and vena cava system in a few patients with patent foramen ovale, which further induces cerebral artery embolism. [ 20 ] A third possible reason is that during sexual intercourse, cerebral oxygen demand can increase, which may induce the deterioration of poorly perfused brain tissue and turn it into infracted tissue. Lastly, elevation of sympathetic nerve activity during sexual intercourse may be accompanied with cerebral arteriospasm, which further aggravates cerebral ischemia.…”
Section: Discussionmentioning
confidence: 99%